2012
DOI: 10.1007/s00417-011-1857-8
|View full text |Cite
|
Sign up to set email alerts
|

Cone-rod dystrophy can be a manifestation of Danon disease

Abstract: BackgroundDanon disease is a neuromuscular disorder with variable expression in the eye. We describe a family with Danon disease and cone-rod dystrophy (CRD).MethodsAffected males of one family with Danon were invited for an extensive ophthalmologic examination, including color vision testing, fundus photography, Goldmann perimetry, full-field electroretinogram (ERG), and SD-OCT. Previous ophthalmologic data were retrieved from medical charts. The LAMP2 and RPGR gene were analyzed by direct sequencing.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 9 publications
(10 reference statements)
1
38
0
Order By: Relevance
“…Specifically, ventricular (Hedberg Oldfors et al, 2015;Miani et al, 2012;Maron et al, 2009;Lobrinus et al, 2005) and atrial (Charron et al, 2004) arrhythmias have both been reported and are often severe, even in women (Miani et al, 2012). Additionally, individuals with Danon disease can also develop (usually relatively mild) skeletal myopathy (80-90% of males), primarily mild cognitive defects and learning disabilities (70-100% of males), and visual problems (69% of males) (Thiadens et al, 2012;Schorderet et al, 2007;Prall et al, 2006;D'souza et al, 2014). For a complete and recent review of clinical descriptions of affected individuals, see D'souza et al (2014).…”
Section: Clinical Manifestations Of Danon Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, ventricular (Hedberg Oldfors et al, 2015;Miani et al, 2012;Maron et al, 2009;Lobrinus et al, 2005) and atrial (Charron et al, 2004) arrhythmias have both been reported and are often severe, even in women (Miani et al, 2012). Additionally, individuals with Danon disease can also develop (usually relatively mild) skeletal myopathy (80-90% of males), primarily mild cognitive defects and learning disabilities (70-100% of males), and visual problems (69% of males) (Thiadens et al, 2012;Schorderet et al, 2007;Prall et al, 2006;D'souza et al, 2014). For a complete and recent review of clinical descriptions of affected individuals, see D'souza et al (2014).…”
Section: Clinical Manifestations Of Danon Diseasementioning
confidence: 99%
“…Clearly, further investigation is needed to better understand the pathological phenotype in the brain. Some clinical studies have described the ophthalmic manifestations of individuals with Danon disease (Thiadens et al, 2012;Prall et al, 2006;Lobrinus et al, 2005). Both male individuals with Danon disease and female carriers have been found to have retinopathy, including peripheral pigmentary retinopathy (Prall et al, 2006) and peripheral 'salt-and-pepper' retinopathy (Schorderet et al, 2007;Thiadens et al, 2012), although sometimes the condition is milder in females.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Thiadens and colleagues report ophthalmoscopic findings of macular disruption and physiologic findings of cone-rod dystrophy in two of four cousins from a family with Danon disease, a rare X-linked disorder characterized by muscle weakness, cardiomyopathy, and mental impairment, which has been mapped to mutations in the lysosomeassociated membrane protein gene, LAMP2 (OMIM #300257) [1].…”
mentioning
confidence: 99%